2022
DOI: 10.3390/w14121972
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Hydro-Geochemical Processes Influencing Groundwater Quality in Rural Areas: A Case Study of Soutpansberg Region, Limpopo Province, South Africa

Abstract: Groundwater is often the main or only source of fresh water supply in arid to semi-arid rural areas owing to decreasing rainfall patterns, reduced availability of surface water and socioeconomic activities. It is important to understand the hydro-geochemical processes influencing groundwater quality for improved management and sustainability of resources and to improve rural livelihoods. To understand the hydro-geochemical process influencing the hydro-geochemistry of the Soutpansberg region, this study assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…As per Moroccan standards, 29 samples from wells were permissible and 16 samples from wells were not permissible for domestic use (Figure 3). Additionally, Table 5 displays the classification according to Handa (1969), revealing that 16% of the sampled locations were in a questionable state, posing concerns for both drinking and irrigation purposes [26].…”
Section: Hydrochemistrymentioning
confidence: 99%
“…As per Moroccan standards, 29 samples from wells were permissible and 16 samples from wells were not permissible for domestic use (Figure 3). Additionally, Table 5 displays the classification according to Handa (1969), revealing that 16% of the sampled locations were in a questionable state, posing concerns for both drinking and irrigation purposes [26].…”
Section: Hydrochemistrymentioning
confidence: 99%
“…Even though the anthropogenic pressure is increasing in the groundwater, in some cases natural pollutants are occurring [11]. The quality of groundwater is mainly influenced by over chemical fertilization [12][13][14][15][16][17], a hydrogeochemical process in aquifers [18][19][20][21], precipitation [22][23][24], land use and cover [25][26][27], and mining activities [28]. Apart from these, one of the major reasons for this contamination is improper irrigations from canals containing urban and industrial effluent and poor drainage [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The temporal changes in the origin of the recharged water and hydrological human factors may also cause periodic changes in groundwater quality 5 . Thus, in order to ensure the quality of groundwater, previous research has recommended that scientific investigations should be used as a decision support system for policy adoption and groundwater designation in rural arid to semi-arid environments 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Collins Chabane municipality covers an area of approximately 5003 km 2 with an estimated population of 347,975. Research has shown that in the Soutpansberg region (which includes Vhembe district) factors such as weathering of silicates, ion exchange processes as well as dissolution of carbonates and halite minerals are hydro-geochemical processes which influence the quality of groundwater 7 . The main land use activities are residential settlements, agriculture and natural forests.…”
Section: Introductionmentioning
confidence: 99%